2019
DOI: 10.1111/risa.13340
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Operational and Organizational Aspects in Interdependent Infrastructure Network Recovery

Abstract: Managing risk in infrastructure systems implies dealing with interdependent physical networks and their relationships with the natural and societal contexts. Computational tools are often used to support operational decisions aimed at improving resilience, whereas economics-related tools tend to be used to address broader societal and policy issues in infrastructure management. We propose an optimization-based framework for infrastructure resilience analysis that incorporates organizational and socioeconomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 37 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…The failure model leverages 'geographically correlated' failures, which have been extensively used in prior work both in the computer science [10] and civil engineering communities [1]. At an abstract level, given a disaster scenario o ∈ O, some set of edges I ⊆ E fail.…”
Section: B Failure Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure model leverages 'geographically correlated' failures, which have been extensively used in prior work both in the computer science [10] and civil engineering communities [1]. At an abstract level, given a disaster scenario o ∈ O, some set of edges I ⊆ E fail.…”
Section: B Failure Modelmentioning
confidence: 99%
“…Inferring network states from partial observations is an important problem in many applications, such as in epidemics, social networks and Internet/AS graphs. Consider critical infrastructure networks like water distribution system or electric grids -their rapid functional restoration is a priority right after a disaster such as an earthquake [1]. The sparse installation of real time monitoring systems installed in these networks (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…M any modern human-made systems, e.g. critical infrastructures integrating operations of vital societal physical and cyber services such as power systems, telecommunication, and transportation, as well as a broad range of natural phenomena from human brain functionality to socioenvironmental ecosystems and virus-host interactomes, exhibit a sophisticated, highly interdependent structure (1)(2)(3)(4)(5)(6)(7). Modeling such interdependency can be addressed with multilayer graphs, resulting in a recent surge of interest in the interdisciplinary analysis of complex multilayer networks.…”
mentioning
confidence: 99%
“…Infrastructure networks interact with each other through interdependencies which are bidirectional interactions across individual networks that influence the overall system operations. Accurate assessment of the system-level performance of interdependent infrastructure networks is essential to the strategic allocation of resources that maintain and protect these systems as well as accelerate their recovery after disruptions [5], [6]. Ideally, the systemlevel performance would be evaluated using real networks where complete information is available on the network topology, spatial characteristics, and operational parameters, such as capacity and flow within individual networks and across networks through interdependent links [7], [8].…”
mentioning
confidence: 99%
“…However, data on the topology and flow of critical infrastructure are typically not publicly available due to privacy and security concerns [9]. Additionally, information on the presence and importance of interdependent links is usually not available due to the decentralized management and lack of coordination across different infrastructure sectors [5]. Ex-post disaster studies have revealed that interdependencies across infrastructure sectors do not behave as expected [10].…”
mentioning
confidence: 99%